Pengaruh Penggunaan Media Interaktif Video Animasi Berbantuan Doratoon Melalui Pendekatan TPACK Terhadap Hasil Belajar Siswa Kelas X SMA Negeri 2 Samarinda Pada Materi Ekosistem - Anggreni, Regia Dwi; Jailani; Kurniawati, Zenia Lutfi; Maasawet, Elsje Theodora; Makkadafi, Suparno Putera (PendIPA Journal of Science Education, 2025)
This study aimed to determine the effect of using interactive media animated videos assisted by Doratoon through the TPACK approach on the learning outcomes of class X students of SMA Negeri 2 Samarinda on ecosystem material. This type of research used a quantitative approach with a quasi-experimental method with a research design, namely non-equivalent control group design. The results obtained from the N-Gain test showed the Mean N-Gain value in the experimental class was 0.40 and in the control class was 0.32 which was included in the moderate category and the results of the T-test with a significance value of 0.014 <0.05. Based on these results, it can be concluded that there is an effect of using interactive media animated videos assisted by Doratoon through the TPACK approach on the learning outcomes of class X students of SMA Negeri 2 Samarinda on ecosystem material.